Importance of the statement of reasons for decisions - Liza Castillo, Luis Manuel (2022)
The due motivation for issuing decisions is the constitutional right of citizens to know the factual and legal reasons that the authorities and officials, especially those of the State apparatus, adopt to resolve claims, where their interests are included. This right is a component of the due process, also called fair process, an expression of effective procedural protection. There is a gender-to-species relationship between both concepts and, consequently, they are closely linked; therefore, undue motivation would be a flagrant violation of citizens’ rights. In this line of ideas, one constantly hears about the filing of appeals against decisions issued because citizens are not satisfied with them, one of the arguments being the lack of motivation, for allegedly having violated substantive and procedural guarantees in the course of the process. In some cases, the appeals are admitted by the higher instance, when it is verified that, in fact, those responsible for deliberating the case acted with disregard in normative and procedural terms, projecting a bad image of the institution to which they belong. Thus, this context motivated the development of this paper, whose objective has been to describe, based on the academic legal opinion and jurisprudence, especially from the Constitutional Court, the characteristics of an unreasoned decision. It has been found that the operator of the proceedings may incur certain vices of justification, making defective or insufficient motivations that do not have relationship between the petition and the decision, almost with the absence of internal logical reasoning and little factual and legal corroboration. These anomalies would reveal that, in some cases, there has not been a proper appreciation of the facts or that the verification and valuation of the evidentiary material were not adequate, generating an invalid decision whose sanction is the nullity and the consequent regularization of the proceedings. It is evident, in turn, that the conduct of the case was irregular and, therefore, affected the interests and expectations of its holders. This situation should not arise, hence the importance of knowing the peculiarities of each of them to detect and report their existence, so that the corresponding instance declares their nullity, as well as to make the pertinent observations to the official who acted improperly, notwithstanding the fact that, ex officio or ex parte, depending on the seriousness of the facts, the records be submitted to other instances so that they can rule on other responsibilities of the official.